Aspects Of Taxonomy And Population Parameters Of Holothuroid (Aspidochirotida: Holothuroidea) In Pulau Kapas, Terengganu, Malaysia - Siti Nuraini, (1995)

(untitled)
This study aimed to investigate some aspects of the taxonomy of holothurian species and population parameters of the dominant species found in Pulau Kapas. Observations by SCUBA on the density and abundance of holothurians were carried out using transect lines in five stations once a month for 11 months, from March 1993 to May 1994, except the months of October 1993 to January 1 994. Data on abundance of holothurians were recorded underwater.Ten species were identified : Holothuria atra, H. edulis, H. hilla, Stichopus chloronotus, S. variegatus, Stichopus sp. , Actinopyga lecanora, A . echinetes, A . miliaris and Bohadschia marmorata. One species of the genus Stichopus could not be identified to the species level . The composition of spicules of the four dominant species did not show any significant difference in most parts of the body such as anterior, posterior, mid dorsal and mid ventral. Of the ten species, H.atra was the most dominant species. It constituted 50 .61 % of total holothurians recorded at study sites. The next abundant species were S. chloronotus (27.13%) and H. edulis (19.51%). Other holothurians were less than 3% of the total holothurians counted in the study areas. The mean density at the five stations showed variation. The high est mean density was recorded at inner zone of Station 3 (244. 64ind.250m-2), follow ed by middle zone of Station 5 (227. 18 ind.250m-2), middle zone of Station 5 (205. 18 ind.250m-2), inner zone of Station 5 (180 .36ind .250m -2 ) and the low est was found at inner zone of Station 2 (2.09ind.250m-2) The abundance of holothurians species, i . e H. atra and S. chloronotus was influenced by bottom substrate. H. atra preferred sand habitat while,